First environmental monitoring of offshore gas drilling discharges in the Deltana Platform, Venezuela - E García; A Cróquer; C Bastidas; D Bone; R Ramos (Ciencias Marinas, 2011)
The benthic macrofauna of two Deltana Platform offshore gas wells was assessed for the first time in Venezuela and correlated with changes in sediment chemistry after exploratory perforation. A gradient analysis was performed at four distance intervals from the perforation site to 1000 m away. At the Ballena well, samples were collected 15 days, 13 months, 19 months, and 30 months after the perforation at 190 m depth. At the Cocuina well, sampling occurred immediately before, and 15 days and 12 months after the perforation at 350 m depth. Principal component analysis and multidimensional scaling were used to assess spatial and temporal patterns of environmental and biotic variables. The temporal pattern was clear, as differences between samples decreased with time after perforation. The results suggest that drilling muds initially changed the chemistry of sediments, but that these changes apparently disappeared approximately two years after perforation and were homogenous at a spatial scale of up to 1 km from the perforation site. A larger spatial scale and more frequent monitoring would be necessary to further understand the potential mechanisms underlying the dispersion and transportation of drilling fluids and muds. This study provides baseline data and the first desciption of the relevant spatial and temporal scales for monitoring the potential effects of chemicals associated with the exploration of offshore gas in Venezuela.